GAMBARAN PENGETAHUAN SISWI TENTANG MENARCHE DI SD NEGERI 1 KEPRABON POLANHARJO KLATEN - Rohmawati, Wiwin; Wahyuningsih, Astri; Hartati, Lilik; Adi Anggreini, Linda (Universitas Muhammadiyah Klaten, 2023)
Background: Menarche is a term for menstruation which occurs for the first time between the ages of 9 – 16 years. Purpose: To find out the description of the knowledge of students at SD Negeri 1 Keprabon Polanharjo Klaten. Method : The method of this research is cross sectional. The population in this study were 32 female students. Sampling using total sampling, namely by taking all members of the population as respondents. The number of samples in this study were 32 female students. The instrument used in this research is a questionnaire. Results: The results in this study were that the majority of respondents had a less knowledge level of 18 people. Conclusion: The conclusion of this study is that elementary school students' knowledge about menarche is still low with the result that the level of knowledge of students is in the less category, namely 18 students.